The Role of Marketing Mix on Public Interest of Banking Credit Submission Application - Cynthia Sari Dewi; Wanda Gema Prasadio Akbar Hidayat (Jurnal Sistim Informasi dan Teknologi, 2023)
The Indonesian economy benefits from the expansion of the banking sector as a financial institution. Currently, a huge market share makes it simple for corporate players to expand in Indonesia's banking industry. This study was created to see if the public's interest in applying for credit at the Bank was influenced by the marketing mix. One hundred bank customers make up the sample. A questionnaire is used to gather the required information. Multiple regression analysis is the data analysis technique used to identify the relationship between the variables. The study's findings demonstrate that the marketing mix significantly influences people's desire to apply for credit at the Bank.